Strategies for Successful Entrepreneurship in a Dynamic Business Landscape - Sulastri, Lani (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This study investigates the strategies underpinning successful entrepreneurship within the dynamic business landscape. The research aims to provide insights into opportunity identification, resource mobilization, strategic decision-making, market positioning, and adaptation to change for aspiring and existing entrepreneurs. Research Design and Methodology: A systematic literature review was conducted, analyzing relevant studies to synthesize critical themes and findings. The review focused on theoretical frameworks and empirical evidence from various disciplines, employing a thematic analysis to identify recurring patterns and concepts. Findings and Discussion: The findings highlight the importance of strategic orientation and resource orchestration in entrepreneurial success. Strategic orientation involves aligning entrepreneurial actions with market opportunities and competitive advantages, while resource orchestration emphasizes effective mobilization and utilization of internal and external resources. The dynamic capabilities perspective underscores the need for adaptability and flexibility in responding to environmental changes. Additionally, the literature emphasizes the critical role of strategic agility, resourcefulness, and a holistic approach to entrepreneurship in navigating the complexities of the modern business environment. Implications: The study offers actionable recommendations for entrepreneurs, policymakers, and scholars, emphasizing the integration of strategic vision, resource management, and dynamic capabilities. Entrepreneurs are encouraged to cultivate strategic agility and resourcefulness to adapt and thrive amidst uncertainty and change. Future research should explore innovative approaches to strategic entrepreneurship that leverage emerging technologies, global networks, and sustainable practices, advancing our understanding of entrepreneurial strategies in a rapidly evolving business landscape.